The Love and Fool Tragedy in Ã¢â‚¬Å“King LearÃ¢â‚¬Â Drama by William Shakespeare - Wahidah, Nurul (Universitas Hamzanwadi, 2018)
Literary work is one of the ways to show some phenomena in this world. Social condition in one country or city can be read in a novel or drama. All of the events and situation at the time become basic idea for author to elaborate his idea through imagination. The story which appeared in that work will be didactic matter for some people. The story also can be end by happy catastrophe or sad. The purpose of this written is to know and to gain social event that happened behind the story. The only key to get the meaning of that story is by reading process. Â Beside that through reading, the meaning of the story in that work will be emerged. Â Reading is a very important action to check the meaning of literary work or playwright. In this drama the story talks about foolish character which cannot get happiness. The story is so sorrowful and full of tragedy. The main character feels sadness and hopeless.Â Without reading the meaning of that drama cannot be understood. Â